WNISEF’S ACTIVITIES IN SOUTHERN UKRAINE FROM (2015–2021) (Південний архів (історичні науки), 2026)
The aim of this article is to provide a comprehensive analysis of the impact of international technical assistance programs implemented by the American Western NIS Enterprise Fund (WNISEF, which currently operates as the Ukraine-Moldova American Enterprise Fund) on the socioeconomic development and profound transformation of local communities in the southern regions of Ukraine (Mykolaiv, Odesa, and Kherson regions) in 2015–2021. The methodological basis of this study is grounded in the fundamental principles of historicism, scientific objectivity, and a systematic approach. To achieve the set goal, general scientific methods of analysis, synthesis, and comparison were actively employed. In addition, a modern interdisciplinary approach was applied to comprehensively study the complex mechanisms of interaction between international financial institutions and local authorities, business representatives, and civil society organizations within the framework of implementing innovative initiatives. The scientific novelty of the article lies in its detailed focus on a little-studied aspect – the regional specifics of the Fund’s work directly in southern Ukraine. This work introduces, for the first time, up-to-date and systematized data on the actual effectiveness of economic and social reforms in Ukrainian communities in the period prior to the full-scale invasion, revealing a unique mechanism of how international technical assistance influences local development. The purpose of this article is to provide a comprehensive analysis of the impact of international technical assistance programs implemented by the American foundation Western NIS Enterprise Fund (WNISEF, which currently operates as Ukraine-Moldova American. The paper provides a detailed analysis of WNISEF’s key areas of activity after 2014, when comprehensive support for decentralization and institutional strengthening became a strategic priority. It is demonstrated that the Fund played a significant role in modernizing the educational infrastructure of the South by funding hub rural schools under the “Pilot 24” initiative. A substantial contribution to urban development is highlighted through the example of institutional support for the Mykolaiv Development Agency. The successful implementation of large-scale educational programs was noted: the establishment of the Mykolaiv branch of the Ukrainian Academy of Leadership (UAL) and support for free IT training for schoolchildren. Significant attention was paid to stimulating innovative business through investments in technology startups, as well as the DREAMactions microgrant initiative for social projects. The author concludes that cooperation between influential international organizations, local government bodies, and community representatives has become an extremely effective tool for stimulating sustainable regional development. And the innovative projects implemented by WNISEF serve as a vivid example of effective collaboration that ensures the irreversibility of transformational processes and can be fruitfully utilized in shaping future reconstruction strategies.
Keywords: WNISEF, Southern Ukraine, local self-government, technical assistance, socioeconomic reforms, Mykolaiv Development Agency, USAID, regional development